2009
DOI: 10.1179/136485909x451825
|View full text |Cite
|
Sign up to set email alerts
|

Potentially pathogenicAcanthamoebain swimming pools: a survey in the southern Brazilian city of Porto Alegre

Abstract: Between May 2006 and March 2007, 65 water samples were collected from both heated and unheated swimming pools in the city of Porto Alegre, the capital of the Brazilian state of Rio Grande do Sul. The aim was to explore the problem posed by, and the pathogenic potential of, Acanthamoeba in the pools. Free-living amoebae in the samples were isolated by culture with Escherichia coli and identified from trophozoite and cyst morphology and the results of a PCR with Acanthamoeba-specific oligonucleotide primers. Pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…During the last few years, molecular techniques (PCR) are increasingly being used in the identification of the genotype (Booton et al 2005, Caumo et al 2009, Edagawa et al 2009, Goldschmidt et al 2012, Howe et al 1997, Itahashi et al 2011, Jain and Tilak 2011, Laummaunwai et al 2012, Le Calvez et al 2012. Our results confirmed the usefulness of PCR for the early, rapid and sensitive diagnosis of pathogenic Acanthamoeba spp.…”
Section: Discussionsupporting
confidence: 74%
“…During the last few years, molecular techniques (PCR) are increasingly being used in the identification of the genotype (Booton et al 2005, Caumo et al 2009, Edagawa et al 2009, Goldschmidt et al 2012, Howe et al 1997, Itahashi et al 2011, Jain and Tilak 2011, Laummaunwai et al 2012, Le Calvez et al 2012. Our results confirmed the usefulness of PCR for the early, rapid and sensitive diagnosis of pathogenic Acanthamoeba spp.…”
Section: Discussionsupporting
confidence: 74%
“…has been identified in many countries around the world for example in Bulgaria (Tsvetkova et al 2004), Osaka (Japan) (Edagawa et al 2009), USA (John and Howard 1995;Ettinger et al 2003;Shoff et al 2008;Stockman et al 2011;Mahmoudi et al 2012), Taiwan (Hsu et al 2009), Brazil (Caumo et al 2009;Magliano et al 2009), South Korea (Jeong and Yu 2005), and Switzerland (Gianinazzi et al 2009). …”
Section: Discussionmentioning
confidence: 97%
“…In this study, the most prevalent genus found was Acanthamoeba. Caumo et al (2009), evaluating the presence of Acanthamoeba in swimming pools, found that some water samples studied were positive for freeliving amoebae, all identified as belonging to the genus Acanthamoeba. The characterization of Acanthamoeba isolates by thermal and osmotolerance assays indicated that some of the isolates were potentially pathogenic.…”
Section: Discussionmentioning
confidence: 99%